Photothermal‐Responsive Soluble Microneedle Patches for Meibomian Gland Dysfunction Therapy - Fei Yu; Xuan Zhao; Qian Wang; Yifei Niu; Peng Xiao; Jinze Zhang; Keyi Fei; Yuancong Huang; Liu Liu; Po‐Han Fang; Xinyue Du; Weihua Li; et al. (Advanced Science)
Abstract Meibomian gland dysfunction (MGD) is a leading cause of evaporative dry eye disease, presenting a challenge for targeted treatment. Traditional topical ocular drug delivery methods often fail to effectively reach the meibomian glands (MGs). To address this, the study has developed a soluble microneedles (MN) patch comprising poly(vinyl alcohol), cyclodextrin modified polyacrylic acid, and new indocyanine green. This innovative MN patch facilitates the transdermal release of peroxisome proliferator‐activated receptor gamma (PPAR‐γ) agonists, such as rosiglitazone in response to near‐infrared ray induced temperature changes. By safely optimizing temperature, the patch effectively liquefied meibum lips, thereby alleviating duct obstruction while releasing the drug. MN patches exhibit sufficient mechanical strength for effective skin penetration, and its biosafety for eyelid application has been rigorously assessed in vitro and in vivo. The therapeutic efficiency of rosiglitazone loaded MN (ROSI‐MN) treatment for MGD is evaluated in high‐fat mice. After three months of treatments, ROSI‐MN administration significantly alleviated MGD clinical manifestations, including ocular surface damage, lipid deposits, glandular hypertrophy, and inflammatory infiltration, ultimately improving the microstructure and biofunction of MGs. In conclusion, the soluble MN patches hold promise as an effective drug delivery strategy for treating ocular surface diseases beyond MGD.